Comparison of Doppler waveform and mean velocity of hepatic vein in cirrhotic patients with healthy subjects and their correlation with severity of cirrhosis - Islam, Mahzabeen; Ahmed, Akhter Uddin; Mohiuddin, AS (Community Based Medical Journal, 2014)
This descriptive study was carried out in the Department of Radiology and Imaging, BIRDEM (Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorder) Dhaka during the period of 1st June 2008 to 30th May 2009, to compare the pattern of the Doppler waveform and mean velocity of hepatic vein between healthy subjects and that in cirrhotic patients and to detect possible differences and also to assess the accuracy of the detection of changes in hepatic vein waveform and mean velocity for the diagnosis of liver cirrhosis. A total of 40 cirrhotic patients and 40 healthy subjects were enrolled in this study. Doppler waveform was done in all the patients and the healthy subjects. The mean hepatic vein velocity (MHVV) was 12.22±4.22 cm/sec and 5.17±1.19 cm/sec in case and healthy group respectively. The mean MHVV difference was significantly (p<0.001) higher in case group. 37.5% patient had wave form HV-0 and HV-1 and 25.0% had wave form HV-2 in case group, however, in healthy group all subjects had wave form HV-0 and the difference was statistically significant (p<0.05) between case and healthy. In Child's class A wave form HV-0 was found in 75.0%, HV-1 was 25.0% and HV-2 was not found in case group. In Child's class B wave form HV-0 was found in 21.4%, HV-1 was 71.5% and HV-2 was 7.1%. In Child's class C wave form HV-0 was not found, HV-1 was 10.0% and HV-2 was 90.0%. The and the difference was statistically significant (p<0.05) among the different grading level with wave form. In Child's class A the mean velocity was 9.18±1.81 cm/sec and velocity ranged from 7.5 to 14.2 cm/sec. In Child's class B the mean velocity was 11.26 ±1.81 cm/sec and velocity ranged from 7.5 to 14.2 cm/sec. In Child's class C the mean velocity was 18.44±1.91 cm/sec and velocity ranged from 15.5 to 20.9 cm/sec. The mean velocity was statistically significant (p<0.05) among Child's class A, Child's class B and Child's class C. From the above summary and previous study it is observed that there is a significant difference between Doppler waveform and mean velocity of right hepatic vein in cirrhotic patients and in normal subjects. It can be used as a new parameter in the assessment of liver cirrhosis. CBMJ 2014 July: Vol. 03 No. 02 P: 23-28